Fate of river-derived microplastics from the South China Sea: Sources to surrounding seas, shores, and abysses. (1st September 2022) - Matsushita, Kosei; Uchiyama, Yusuke; Takaura, Naru; Kosako, Taichi
Abstract: Microplastics (MPs) in the ocean have been widely recognized as causing global marine environmental problems. To gain a quantitative and comprehensive understanding of oceanic MP contamination, detailed numerical Lagrangian particle tracking experiments were conducted to evaluate the regional oceanic transport and dispersal of MPs in the South China Sea (SCS) derived from three major rivers, Pearl (China), Mekong (Vietnam), and Pasig (the Philippines), which are known to discharge large amounts of plastic waste into the SCS. As previous field surveys have suggested, MP contamination spreads from the surface to the deeper ocean in the water column, we thus considered three types of MPs: (1) positively buoyant (light) MPs, (2) positively buoyant (light) MPs with random walk diffusion, and (3) full 3-D tracking of non-buoyant MPs that are passively transported by ambient currents. Transport patterns of these MPs from the three rivers clearly showed the intra-annual variability associated with seasonally varying circulations driven by the Asian monsoons in the SCS. Many MPs floating during the prevailing southwest monsoon are transported to the northwest Pacific Ocean and the East China Sea through the Luzon Strait and the Taiwan Strait to form MP hotspots . Non-buoyant MPs are broadly transported from the surface layer to depths of approximately 100 m or deeper, where in situ observations are rare. In addition, the buoyant MPs drifting on the continental shelf originating from southern China tend to be pushed toward the shore and beached by northward wind-induced currents more pronouncedly than the non-buoyant MPs. Therefore, the river-derived MPs to the SCS were found to serve as sources to adjacent basins and oceans, to be distributed not only in the upper layer but also in the abyssal ocean (non-buoyant MPs), and to be transported to the shores (buoyant MPs). Graphical abstract: Image 1 Highlights: Particle tracking experiments with 3D high-resolution ocean model were conducted. Microplastic (MP) transport is greatly affected by seasonally varying monsoons. Many MPs from the South China Sea are transported to the surrounding seas. Non-buoyant MPs are broadly transported vertically from the surface to the abysses. Buoyant MPs are more beached than non-buoyant MPs due to wind-induced currents.